Research Note: Coverage of climate change risks in leading Philippine newspapers - Piamonte, Rick-Angelo; Gravoso, Rotacio S. (Annals of Tropical Research, 2008)
The study aimed to find out the coverage of climate change risks in Philippine leading newspapers – Philippine Daily Inquirer, Philippine Star, and Manila Bulletin. The sample issues were from those published from January to December 2007. Results showed that the sample newspaper issues had 401 articles on climate change risks. Of these articles, the biggest number was related to education and the least was species extinction. The one-way ANOVA showed that the three national dailies were not significantly different in terms of the number of climate change risk articles. Results also revealed that the three newspapers did not give prominence to climate change risk articles. Aside from the small space allocated, most of these articles were placed in inside pages. Experts were the most common sources of information for the articles.